The effect of diaphragmatic breathing and diaphragmatic mobilization on physical performance, fear of falling, and quality of life in community-dwelling older adults: A randomized controlled trial - Soyba Nazir; Witaya Mathiyakom; Muhammad Awais Tassawar; Anong Tantisuwat (PLoS ONE, 2026)
Background Falls are a significant health concern among older adults, leading to reduced mobility, fear of falling, and poor quality of life. Diaphragmatic breathing (DB) and diaphragmatic mobilization (DM) may serve as therapeutic interventions to address these issues. Objective This study evaluated the effects of DB and combined DB and DM (DB + DM) on physical performance, fear of falling, and quality of life in community-dwelling older adults. Methods Fifty-four older adults (65–75 years) were randomized into group 1, DB; group 2, DB + DM; and group 3, control groups (18 per group). Interventions were delivered twice weekly for 8 weeks. Outcomes, including balance, gait performance, lower extremity strength, fear of falling (FoF), fatigue, and quality of life (QoL), were measured at baseline, post-treatment (8th week), and follow-up (10th week). Results Significant group-by-time interaction effects (p < 0.05) were observed in all outcome measures except a few domains of Short-form 36 (SF-36). At post-treatment, the mini-BEST scores and the time to complete 5-time sit-to-stand test (5xSTS) of the DB and DB + DM groups did not significantly increase compared to baseline. The timed up-and-go (TUG) scores (η² = 0.279) and gait velocity (GV) (η² = 0.619) of both interventions significantly improved (p < 0.05) from baseline to post-treatment and follow-up. Scores for active balance confidence (ABC) (η² = 0.706), fatigue severity scale (FSS) (η² = 0.584), and specific domains of SF-36, physical function (η² = 0.211), pain (η² = 0.173), and general health (η² = 0.168) showed significant improvements in both intervention groups compared to the control group. Conclusion DB and DB + DM interventions significantly improved gait performance, FoF, fatigue, and QoL in community-dwelling older adults. However, their therapeutic effects on balance were limited and need further investigation.